2000
DOI: 10.1159/000020968
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Uterine Fetal DemiseCaused by Amniotic Band Syndromeafter Standard Amniocentesis

Abstract: The amniotic band syndrome represents a prime example of exogenous disruption of an otherwise normal fetal development. It may be a sequel of invasive diagnostic procedures such as amniocentesis or fetal blood sampling. A 38-year-old gravida II, para II delivered a morphologically normal male stillborn at term. The pregnancy history had been unremarkable but for an early 2nd-trimester amniocentesis. Cause of the intra-uterine fetal demise was noted to be an amniotic band constricting the umbilical cord. An amn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 14 publications
0
19
1
1
Order By: Relevance
“…Some techniques like amniopatch [10] have been attempted to reduce the rate of complications, with variable results. Little or no data are presented on the incidence of PABS, where there is entanglement of fetal parts in a constrictive sheet of detached or ruptured amniotic membrane after invasive procedures such as amniocentesis [11,12,13], amnioreduction [14], or septostomy in twins [15]. In a smaller retrospective study by Habli et al [16] involving 152 patients with TTTS who were treated with SFLP at 16–26 weeks of gestation, 5 cases (3.3%) had PABS.…”
Section: Discussionmentioning
confidence: 99%
“…Some techniques like amniopatch [10] have been attempted to reduce the rate of complications, with variable results. Little or no data are presented on the incidence of PABS, where there is entanglement of fetal parts in a constrictive sheet of detached or ruptured amniotic membrane after invasive procedures such as amniocentesis [11,12,13], amnioreduction [14], or septostomy in twins [15]. In a smaller retrospective study by Habli et al [16] involving 152 patients with TTTS who were treated with SFLP at 16–26 weeks of gestation, 5 cases (3.3%) had PABS.…”
Section: Discussionmentioning
confidence: 99%
“…There have been isolated case reports of constriction band syndrome occurring following intrauterine instrumentation, such as amniocentesis (11)(12)(13)(14)(15), chorionic villus sampling (16) or the placement of an intrauterine contraceptive device (10). No clear causative link has been established, but it is suggested that the instrumentation required in the IVF procedure may have played a role.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there have been reports associating amniotic band syndrome with maternal trauma, oophorectomy during pregnancy (9), intrauterine contraceptive device (10), amniocentesis (11)(12)(13)(14)(15) and chorionic villus sampling (16).…”
mentioning
confidence: 99%
“…In case of a threatened limb amputation in an otherwise normal fetus, fetoscopic release of the constricting band can restore flow, which may improve functional outcome [3,4,5,6,7]. Umbilical cord entrapment, which can cause intrauterine fetal demise, may present as another life-threatening problem [8]. …”
Section: Introductionmentioning
confidence: 99%